2012
DOI: 10.1121/1.3675553
|View full text |Cite|
|
Sign up to set email alerts
|

Re-expansion method for circular waveguide discontinuities: Application to concentric expansion chambers

Abstract: The paper applies the re-expansion method for analyzing planar discontinuities at the junction of two axi-symmetrical circular waveguides. The normal modes in the two waveguides are expanded at the junction plane into a system of functions accounting for velocity singularities at the corner points. As the new expansion has a high convergence order, only a few terms have to be considered for obtaining the solution of most practical problems. This paper gives the equivalent impedance accounting for nonplanar wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…Note that in eigenfunction expansions given by equations ( 12), (13), and ( 23)-( 25), the amplitudes {B n , D n , E n }, n = 0, 1, 2, . .…”
Section: Problem Formulationmentioning
confidence: 99%
See 3 more Smart Citations
“…Note that in eigenfunction expansions given by equations ( 12), (13), and ( 23)-( 25), the amplitudes {B n , D n , E n }, n = 0, 1, 2, . .…”
Section: Problem Formulationmentioning
confidence: 99%
“…By substituting equations ( 12), (13), and ( 23) into equation (30), after simplification through equation ( 27), it is found that:…”
Section: Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…This method entails matching the solutions of the wave equation at the interfaces between different regions of the waveguide, utilizing continuity conditions for both pressure and velocity. The mode-matching technique has gained wide acceptance in waveguide structure analysis due to its accuracy and efficiency, especially in cases involving nonuniform cross-sections and boundary conditions [16][17][18][19][20]. The primary objective of this study is to establish a theoretical framework for analyzing and optimizing the acoustic performance of the waveguide by employing the mode-matching method.…”
Section: Introductionmentioning
confidence: 99%